2019
DOI: 10.7150/jca.27780
|View full text |Cite
|
Sign up to set email alerts
|

The Prospective Value of Dopamine Receptors on Bio-Behavior of Tumor

Abstract: Dopamine receptors are belong to the family of G protein-coupled receptor. There are five types of dopamine receptor (DR), including DRD1, DRD2, DRD3, DRD4, and DRD5, which are divided into two major groups: the D1-like receptors (DRD1 and DRD5), and the D2-like receptors (DRD2, DRD3, and DRD4). Dopamine receptors are involved in all of the physiological functions of dopamine, including the autonomic movement, emotion, hormonal regulation, dopamine-induced immune effects, and tumor behavior, and so on. Increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 131 publications
1
58
0
Order By: Relevance
“…1 DRD2 Overexpression in Human Cancer. The indicated publications for each tumor type were identified through a PubMed search as of July 2020, as well as recent reviews of DRD2 in oncology [19] , [20] . …”
Section: Onc201 Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 DRD2 Overexpression in Human Cancer. The indicated publications for each tumor type were identified through a PubMed search as of July 2020, as well as recent reviews of DRD2 in oncology [19] , [20] . …”
Section: Onc201 Mechanism Of Actionmentioning
confidence: 99%
“…Dopamine and dopamine receptors are secreted and expressed, respectively, by various immune cells. This includes NK and T-cells that can be targeted to modulate tumor immune response [20] , [43] , [44] . Dopamine inhibits NK cell effector function [44] , and DRD2 antagonism has been shown to activate NK cells [43] .…”
Section: Onc201 Mechanism Of Actionmentioning
confidence: 99%
“…Although our understanding of the biology of dopamine receptor signaling in cancer progression is still rudimentary and sometimes controversial, mounting experimental and clinical evidence has indicated that the dysregulation of dopamine receptor signaling is associated with the progression of human cancers, including PCa (35,(57)(58)(59)(60). Some epidemiologic studies further suggested a correlation between psychotic disorders in which dopaminergic drugs are applied and the risk of cancer, of particular note, a reduced risk of PCa (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…DRD2 has been shown to regulate many aspects of tumor behavior, including invasion and migration in cancer cells. Activation of DRD2 by the DRD2-speci c agonist BIM53097 inhibits tumoral pituitary cells migration and invasion by activating the co lin pathway in vitro (45,46). However, downregulation of DRD2 by tri uoperazine and haloperidol also results in decreased invasion and migration in prostate cancer cells, indicating the functional diversity of DRD2 and its downstream targets in different types of cancer (47).…”
Section: Discussionmentioning
confidence: 99%